THE INFLUENCE OF PLASMIDS AND OTHER MGE’S OVER ANTIBIOTIC RESISTANCE IN MULTIDRUG RESISTANT STAPHYLOCOCCUS AUREUS ISOLATED FROM HIV+ PATIENTS - K N, Nihal; Daniel, Betty Bagyam; Varghese, Jancy (LIFE: International Journal of Health and Life-Sciences, 2017)
Bacterial opportunistic infections are common among immunocompromised patients. Antibiotic resistance hinders efforts to treat such infections. Our objectives are to detect the prevalence of Staphylococcus aureus in immunocompromised HIV patients, to analyze their antibiogram, to correlate antibiotic resistance with the presence of plasmids and to identify crucial antibiotic resistance genes and understand their connectivity with MGEs. Bacterial strains were collected from HIV+ve patients. Pure cultures of Staphylococcus aureus were isolated and its clones were selected for further studies. Their Antibiogram and plasmid profiles were analysed. Vancomycin resistant strains were selected and PCR was conducted to trace the presence of Van A in both the gDNA and plasmids. There wasn’t much correlation between antibiotic resistance and plasmid profile. The most resistant strains didn’t have high copy number plasmids than the less resistant ones. Thus Plasmids weren’t the sole determinants of antibiotic resistance. This led us to explore other MGEs that could aid in conferring antibiotic resistance -an MGE that could be stationed on both gDNA & Plasmids. Literature shows that b-lactam resistance is due to transposons. A Tn3 family that’s non-constitutive, replicative DNA transposon. This transposon stays on the gDNA further lowering the possibilities of losing it via vertical gene transfer. VanA is a part of similar transposon Tn 1546 of the Tn3 family. PCR for Van A on Vancomycin resistant strains showed positive results both on gDNA and plasmids. The outcomes open up other possible pathways to tackle MDR strains than antibiotics.